Forecasting Iran national health expenditures: General model and conceptual framework - Mahmood Kazemian; Zhaleh Abdi; Mohammad Meskarpour-Amiri (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Forecasting the future trend of health expenditures is an important step toward sustainable financing of health-care systems. This study aims to develop a conceptual framework for forecasting Iran health spending growth. MATERIALS AND METHODS: At first, we concentrated on the general model and conceptual framework of health expenditure projection by reference to a broad literature review and smart classifications of the origins of health spending and indicators. At the second step, we developed a time series modeling for econometric estimation and forecasting national health expenditure without restrictive assumptions except for current laws and regulatory environment. In the third step, we tested the accuracy of model by forecasting Iran real per capita health expenditures (2017-2025). RESULTS: The results of the literature review represented a distinct classification of the origins of health spending and indicators, applicable to any health system and health spending projection model. Furthermore, the model of expenditure forecasting shows the power of certainty of no spurious estimation, assessment of the normal state of a health system, and test of the accuracy of forecasting results. The projection by the Iranian health system database showed that the real per capita health spending will grow 43 percent till 2025 in the absence of any unforeseen disturbance in the future. CONCLUSIONS: The presented model provides estimates that are compatible with actual trends of health spending and can be applied to forecast health expenditure in the near future. The forecasted image of Iran's health spending growth implies that health authorities need to concentrate more on the growth rate of the health budget and its fiscal space in the near future.